GENETIC AND EPIGENETIC MECHANISMS OF AGING - Novaković, Ivana; Filipović, Tamara; Maksimović, Nela; Nikolic, Dejan (Medicinski podmladak, 2024)
Aging is inevitable and the representation of old people in the population grows. Accordingly, the understanding of genetic factors and physiological mechanisms involved in the process of normal aging is of increasing importance for maintaining the quality of life in old age. Preserving the physiological functions or "health" of old people will reduce pressure on health systems and costs. In this review, in the light of the latest scientific data and hypotheses, some key questions regarding the genetics, biology and physiology of aging are briefly discussed: what is aging, why it occurs and what are the possibilities of delaying and slowing down of aging.
Keywords: aging; genetics; characteristics; causes; delay